A Wide Bandgap Ag/MgO@Fe3O4 Nanocomposite as Magnetic Sorbent for Cd(II) in Water Samples - Hanif, Muddasir; Yasmeen, Kousar; Muhammad, Haji; Shah, Faheem; Hussain, Saqib; Atta-ur-Rehman; Masab, Muhammad; Ali, Syed T.; Tahiri, Iftikhar Ahmad (Current Analytical Chemistry, 2020)
Background: The magnetic nanocomposites are very important as a reusable sorbents for the extraction of Cd(II) and other toxic metals from water samples. Methods: The Ag/MgO@Fe3O4 nanocomposite was synthesized by the coprecipitation method and characterized by the XRD, EDX, SEM, UV-vis spectroscopy and FTIR. This nanocomposite was used to extract Cd(II) from water samples prior to its quantitative analysis with FAAS. Different variables, i.e. pH, temperature, amount of nanosorbent, adsorption/desorption and dilution were optimized. Results: The method was successfully applied to determine Cd(II) in real water samples with excellent recoveries (98%). The present method has lower detection (0.29) and quantification limit (0.97 ng mL-1). Conclusion: The Ag/MgO@Fe3O4 nanocomposite based magnetic extraction is a simple, fast, reproducible, less expansive and efficient technique for the Cd(II) extraction in water samples. The developed sorbent can be recycled and reused (20 times).
Keywords: flame atomic absorption spectrometry (FAAS)